1982
DOI: 10.1073/pnas.79.4.1175
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody to transferrin receptor blocks transferrin binding and inhibits human tumor cell growth in vitro.

Abstract: A murine hybridoma has been obtained that produces a monoclonal antibody against the human transferrin receptor. In contrast to previously characterized monoclonal antibodies that recognize the transferrin receptor, this antibody, designated 42/6, blocks the binding of transferrin to its receptor and inhibits the growth of the human T leukemic cell line, CCRF-CEM, in vitro. Inhibition of cell growth was dose dependent, and as little as 2.5 jtg of purified antibody per ml had a detectable effect, even though tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
145
0
2

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(157 citation statements)
references
References 47 publications
10
145
0
2
Order By: Relevance
“…Malignant lesions rarely occupy more than 20% to 30% of rat liver volume in our experimental conditions (Pascale RM, unpublished results, 1996), and large Tf excess is produced by unaffected liver. 34 Previous work 35 has shown that the prevention of the interaction of Fe 2 -Tf with Tf-R, by anti-Tf-R monoclonal antibodies, results in arrest of in vitro growth of human T leukemia cells. Thus, overexpression of Tf-R with overgrowth, and active internalization of Fe 2 -Tf/ Tf-R complex in HCC, makes Tf-R a possible target for a model system of liver tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant lesions rarely occupy more than 20% to 30% of rat liver volume in our experimental conditions (Pascale RM, unpublished results, 1996), and large Tf excess is produced by unaffected liver. 34 Previous work 35 has shown that the prevention of the interaction of Fe 2 -Tf with Tf-R, by anti-Tf-R monoclonal antibodies, results in arrest of in vitro growth of human T leukemia cells. Thus, overexpression of Tf-R with overgrowth, and active internalization of Fe 2 -Tf/ Tf-R complex in HCC, makes Tf-R a possible target for a model system of liver tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] When intracellular iron is low, the cells must mobilize storage iron and increase uptake of plasma iron. This latter process is favored by a rise in the availability of Tf-R on the cell surface of fast-growing tissues, such as post-partial hepatectomy liver, nodules, and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…One of the consequences of this interaction is an upregulation in cellsurface membrane IL-2-R (20, 21). IL-2 has also been shown (22)(23)(24) to be an important signal in the upregulation of another receptor, the transferrin receptor, which is thought to be important in cellular growth and is found on rapidly dividing cells. A potential mechanism whereby TGF-/3 might inhibit the growth of T cells is by interfering with the normal expression of either of these receptors.…”
Section: Tgf-t3 Suppresses Il-2-dependent T Cell Proliferation and Pamentioning
confidence: 99%
“…A number of claims (Kirch & Hammerling, 1981;Bernstein et al, 1980;Scheinberg & Strand 1982;Miller & Levy, 1981;Ritz et al, 1980;Trowbridge & Lopez 1982;Herlyn & Koprowski, 1981), of therapeutic benefit from the use of MAb in cancer therapy have been reported recently in the literature. Partial successes in tumour systems other than that used here could be attributed to different Ig isotypes, acting through an antibody-dependent cellular cytotoxicity (ADCC) rather than complement-mediated lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although tumourspecific antigens in human tumours (Metzgar et al, 1981;Iwaki et al, 1982;Ball et al, 1982) have not yet been definitely demonstrated, monoclonal antibodies (MAb) highly specific to TAA (Gunn et al, 1981) or to tissue and differentiation antigens (Kirch & Hammerling, 1981) might provide optimal tools to study the anti-tumour efficacy of passive serotherapy (Kirch & Hammerling, 1981;Bernstein et al, 1980;Scheinberg & Strand 1982;Ritz et al, 1981;Trowbridge & Lopez, 1982;Sears et al, 1982).…”
mentioning
confidence: 99%